Surgical Therapy and DH-II-90 Protocol in the Treatment of Hodgkin Disease in Young Adults: an Ecological Study - Oliveira, Barbara Cardoso de (2022)
Introduction: Hodgkin disease (HD) is a pathology that starts in the lymph nodes, develops in the neoplastic tissues and manifests, mainly, in young adults. Objective: To correlate the results of the surgical therapy and the DH- II-90 protocol in young adults affected by HD, and to associate them with the epidemiological profile, the mortality data by the disease and the distribution of physical resources in Brazil. Method: Exploratory ecological study with information collected from the Informatics Department of the National Health System (DATASUS), the National Cancer Institute José Alencar Gomes da Silva (INCA), the National Registry of Health Establishments (CNES) and the SUS Outpatient Information System (SIA/SUS) between 2013 and 2021. The study, therefore, compares the results of surgical therapy and the DH-II-90 protocol associated with epidemiological data, and the protocol is considered the most efficient method, as it produces better results when compared to more invasive methods. Results: The Southeast Region concentrates high number of beds and procedures and stands out due to more expressive numbers of patients diagnosed from 0 to 29 years. In short, crude mortality rates per HD decreased from 1990, the period where the DH-II-90 protocol was applied. Conclusion: This study provides a relevant view on the epidemiological profile of HD and contributes for the comparison between surgical therapy and the DH-II-90 protocol, being possible to conclude that after the application of the protocol, there was a reduction of the mortality rate by HD in Brazil and worldwide.